NOS1-, NOS3-, PIK3CA-, and MAPK-pathways in skin following radiation therapy - Koerdt, Steffen; Ristow, Oliver (Biomarker Research, 2017)
Essential molecular pathways such as the MAPK pathway, NO system, or the influence of PIK3CA as an oncogene are known to regulate fundamental signalling networks. However, few knowledge about their role in the occurrence of wound healing disorders (WHD) following radiation therapy (RT) exists. This study aims to evaluate the expression profiles of specific molecular pathway marker genes.
Gesehen am 05.11.2018